IMPACT OF TAKEOVER PROCESSES ON EMPLOYEES – EVIDENCE FROM FOOD, RETAIL AND FINANCIAL SECTOR - Andrašić, Jelena; Mirović, Vera; Milenković, Nada; Kalaš, Branimir; Pjanić, Miloš (Economics of Agriculture, 2017)
Takeover processes imply integration of different organizational cultures, especially in case of crossborder takeovers. Using a survey questionnaire, authors conducted a research to examine the changes and satisfaction with all interest groups in taken over companies operating in felds of food industry, retail sector and fnancial activity in the Serbian market. Method applied to process the data is discriminant analysis, and research results are presented tabular form as well as graphically in form of ellipses. The aim of the study is to examine the differences of impact of takeover processes on various interest groups of production company, retail chain and fnancial institution and assessment of their satisfaction. Studys contribution is an informative support for managers of both company acquirer and target company in future acquisition processes, because analysis of differences, change and satisfaction of employees provides a concrete answer regarding elements influencing success of takeover process in terms of management of human.